Analysis of Insurance Literacy Levels and Efforts to Prevent Employee Performance Fraud at BUMIDA Insurance Company in Riau Province - Izakiah; Yusriwarti; Suryani (P3M, Sekolah Tinggi Ilmu Ekonomi Pasundan Bandung, 2025)
This study aims to analyze the level of insurance literacy and fraud prevention efforts that affect employee performance at PT. Asuransi Umum Bumida 1967, Riau Province Branch. The background of this study is based on the public's still low understanding of basic insurance concepts, as well as weak awareness of some employees regarding the company's anti-fraud policies. In response to these problems, the company initiated the B-SMART program as a literacy tool that involves university students to educate the public, while also strengthening employees' internal awareness of integrity and control systems. This study used a qualitative approach with a source triangulation method, involving informants from various strategic positions in the company. The results show that the level of insurance literacy among employees is quite good, indicated by an understanding of the benefits, risks, and rights of the policy. However, there is a need to further improve understanding, especially regarding the claims process and policy exclusions. Meanwhile, fraud prevention efforts are considered quite effective, with the implementation of an internal control system, instilling an anti-fraud culture, and providing adequate compensation as work motivation. Overall, the findings indicate that good literacy and appropriate preventive efforts can significantly improve employee performance and maintain the company's sustainability. This research makes an important contribution to understanding the relationship between financial literacy and operational integrity in the insurance industry.